Corpo, dança, educação : Cia. Municipal de Dança de Caxias do Sul - Santos, Carlos Alberto Pereira dos (My University, 2014)
Dissertation is about the concept of the body and its possibilities as a device of development of concepts, statements and education. From the body, dance and education triad, I problematized the possibility of the contemporary body produces thoughts while dancing. In this sense, the ideas of Merleau-Ponty about his own body, as well the researches from Katz and Greiner around corpomídia are references. Contemporary dance is also analyzed as a continuous vector of producing metaphors, which only gain poignancy when incorporated in these bodies that dance. In the unfolding of these actions, appears the pedagogical and educational vector of contemporary dance, which will be analysed through the experience of Caxias do Sul Municipal Dance Co. from conception in 1997 to present time. This training is essencial for upgrading the educational and cultural repertoires of Caxias do Sul, promoting a contaminator action with social, political, educational and cultural aspects.
Esta dissertação estuda a evolução do conceito de corpo e suas possibilidades enquanto dispositivo de elaboração de conceitos, enunciados e educação. A partir do trinômio corpo, dança e educação, problematiza-se a possibilidade de o corpo contemporâneo produzir pensamentos quando dança. Nesse sentido, as ideias de Merleau-Ponty sobre o corpo próprio, bem como as pesquisas de Katz e Greiner em torno do corpomídia são referências. A dança contemporânea também é analisada como incessante vetor de produção de metáforas, que só ganham contundência quando incorporadas nesses corpos que dançam. No desdobramento dessas ações, surge o vetor pedagógico e educativo da dança contemporânea, que será olhada através da experiência da Cia. Municipal de Dança de Caxias do Sul, desde a sua criação, em 1997, até hoje. A formação tem papel fundamental na atualização dos repertórios educativos e culturais de Caxias do Sul, promovendo uma ação contaminatória, com aspectos sociais, políticos, pedagógicos e culturais.
Keywords: Dança - Caxias do Sul (RS); Dança na educação; Corpo humano (Filosofia); Body; Dance; Education